Driving Assessment 2005 : Proceedings of the 3rd International Driving Symposium on Human Factors in Driver Assessment, Trainin 2005
DOI: 10.17077/drivingassessment.1150
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Messages Displayed on Dynamic Message Signs

Abstract: Summary: A human factors study was carried out to help enhance ways to communicate with highway motorists through dynamic message signs (DMS). Overhead mounted DMSs have been increasingly used by highway authorities in the United States to present real-time traffic information and travel advice to motorists. It is critical to post sign messages that can be quickly and clearly understood by motorists, especially in high-volume traffic and construction/repair zones. Properly worded and formatted sign messages co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
10
2
Order By: Relevance
“…In order to identify the subjective attitude and preference of drivers for VMS formats, Yang et al (2005) concluded that most subjects preferred the green and amber color combination. Moreover, if only one color was used, red was found to be the least preferred option.…”
Section: Subjective Measure For Vms Contents and Formatsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to identify the subjective attitude and preference of drivers for VMS formats, Yang et al (2005) concluded that most subjects preferred the green and amber color combination. Moreover, if only one color was used, red was found to be the least preferred option.…”
Section: Subjective Measure For Vms Contents and Formatsmentioning
confidence: 99%
“…This includes: (i) revealed preference (RP) questionnaire surveys (Chatterjee et al, 2002;Kilpeläinen and Summala. 2007;Wang et al, 2009;Hassan and Abdel-Aty, 2011), stated preference (SP) questionnaire survey (Benson, 1996;Emmerink et al, 1996;Wardman et al, 1997;Al-Madani andAl-Janahi, 2002a, 2002b;Hassan and Abdel-Aty, 2011;Gan and Ye, 2011;Jindahra and Choocharukul, 2013;Spyropoulou and Antoniou, 2014;Ronchi et al, 2016) and a combination of SP and RP survey (Al-Deek et al, 2012), (ii) driving simulators (Mahmassani and Chen, 1991;Wang and Cao, 2005;Lai, 2008Lai, , 2012Shinar and Vogelzang, 2013;Williams et al, 2015;Sharples, et al, 2016;Roca et al, 2018 ), and (iii) the combination of questionnaire survey and driving simulators (Yang et al, 2005;Wang et al, 2007;Lai, 2010;Cristea and Delhomme, 2014;Zhong et al, 2016).…”
Section: Research Approaches In Designing Vmsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, reading time for DMSs is higher than for traditional static signs because motorists see static signs regularly, and drivers may rely on memory more than actually reading the sign to obtain the message (Wang & Cao, 2005;Yang et al, 2005). A message presented by a static sign is consistent, whereas the message conveyed by a DMS may change based on a number of factors, requiring driver attention with each encounter (Dudek, 2004).…”
Section: Dmssmentioning
confidence: 99%
“…There is also a wealth of literature that describes the appropriate frame scheme, color combinations, and wording to increase the readability of DMS among drivers (e.g., Yang et al, 2005). Other key design parameters include the type of display technology (lightemitting, light-reflecting, etc.…”
Section: Dmssmentioning
confidence: 99%